Structural variations in metal complexes of a tertiary α-hydroxyoxime - D'Alessio, D.; Lombardo, D.; Vaughan, J.; Skelton, B.; Barnard, K.; Ogden, Mark (Royal Society of Chemistry, 2015)
Despite the long term interest in hydroxyoximes as metal ion extractants, there is a lack of information on the possible coordination modes these ligands can assume, particularly in concert with a co-ligand. This is pertinent to the use of these extractants in synergistic systems, where a combination of extractants can achieve commercially useful results. We report here the structures of some metal complexes (M = Mn, Co, Ni, Cu, and Zn) with (1-hydroxycyclohexyl)-phenyl ketone oxime. The results demonstrate that this ligand can support complexes ranging from mononuclear to trinuclear, in association with anionic and neutral co-ligands in some cases. While these results have been obtained in the solid state, they illustrate a range of possible species that may be formed in extractant solutions.